(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2018)
The effects of the synthetic insecticide Eforia 043 ZK (thiamethoxam+lambdacyhalothrin), applied alone and at 1/5 and 2/5 reduced doses in a mix with the mineral oil Akarzin, on Tychius flavus Beck. (Coleoptera: Curculionidae), Adelphocoris lineolatus Goeze (Hemiptera: Miridae), Acyrthosiphon pisum Harr. (Hemiptera: Aphididae), harmful thrips (Thysanoptera) and cicadas (Hemiptera: suborder Auchenorrhyncha) were studied. The efficacy of Eforia (applied alone and in reduced doses) was significantly higher against A. pisum, followed by A. lineolatus and harmful thrips, compared to cicadas. The insecticidal action of Akarzin had a better protective effect against A. pisum, followed by A. lineolatus, in comparison with thrips and cicadas. Combined application of the broad-spectrum insecticide Eforia provided good control against insect pests. The mix of Eforia’s reduced 1/5 dose with the mineral oil showed the highest toxicity throughout the reporting period. Eforia applied at the reduced dose of 2/5 with Akarzin followed in efficacy. A synergistic effect was observed in combinations and was defined as subadditive synergism. Reduced dosage of Eforia and decrease in negative environmental impact of the plant protection products is a friendly approach to integrated pest control. It is important to apply innovative formulations of plant protection products that are safer both for plants and the environment.